2012
DOI: 10.5144/1658-3876.2012.42
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 study of the combination of gemcitabine and cisplatin in patients with locally advanced or metastatic breast cancer previously treated with anthracyclines with/ without taxanes

Abstract: The results of this study indicate that gemcitabine and cisplatin were active and generally well tolerated in pretreated patients with locally advanced or metastatic breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…It is used in combination with other drugs for the treatment of locally advanced or metastatic non-small-cell lung cancer, bladder cancer, and ovarian cancer, and as a single agent for the treatment of adenocarcinoma of the pancreas 4. Clinical studies have also demonstrated its extensive activity against breast carcinomas, including male breast cancer,5 metastatic breast cancer, and triple-negative breast cancer 6,7. In recent years, gemcitabine resistance has emerged and has become a serious concern in clinical practice; however, the exact mechanism of gemcitabine resistance in breast cancer is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It is used in combination with other drugs for the treatment of locally advanced or metastatic non-small-cell lung cancer, bladder cancer, and ovarian cancer, and as a single agent for the treatment of adenocarcinoma of the pancreas 4. Clinical studies have also demonstrated its extensive activity against breast carcinomas, including male breast cancer,5 metastatic breast cancer, and triple-negative breast cancer 6,7. In recent years, gemcitabine resistance has emerged and has become a serious concern in clinical practice; however, the exact mechanism of gemcitabine resistance in breast cancer is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Although effective, most combinations have adverse side effects, including neutropenia, neuropathy, and cardiotoxicity, and many tumors still progress to metastasis 4 , 9 . Regimes with a more tolerable toxicity tend to yield a much lower overall response rate 10 , 11 . There is, therefore, a great need to improve efficacy of existing combination therapies by mitigating toxic side effects and improving complete response rates.…”
Section: Introductionmentioning
confidence: 99%
“…A study from Egypt reported on gemcitabine and cisplatin in locally advanced or metastatic BC after previous anthracycline therapy. In 132 patients, there was a 33% response rate and a 46% rate of stable disease was seen [38]. A study from Egypt compared anthracycline-based chemotherapy with or without docetaxel in estrogen receptor-positive pT1-2 BC (n = 60).…”
Section: Surgery and Adjuvant Treatment Of Bcmentioning
confidence: 99%